The Utilization of Health Care Services and their Determinants Among the Elderly Population of Dhulikhel Municipality - Sanjel, S; Mudbhari, N; Risal, A; Khanal, K (Kathmandu University Medical Journal, 2012)
Background Population ageing is a common problem faced in many countries world-wide. Due to physiological and biochemical changes in the elderly, increased incidence of diseases is observed. There is often low use of health services by the elderly for a variety of reasons. Objective To examine the status of health care utilization and to determine the factors associated with utilization of health care among the elderly population of Dhulikhel Municipality. Methods A quantitative descriptive-cross sectional study, with a total number of 200 elderly people residing in Dhulikhel Municipality, was selected for the study. Data were collected across the months of June - July 2011 applying two-staged cluster and systematic random sampling method. Both descriptive and inferential statistics were measured. Results Sixty eight percent of the elderly visited medical personnel in the past year. Eight percent of them visited the emergency department where most of them reported with symptoms attributed to heart disease. Among 200 elderly, 12.5% of them were admitted to the hospital and 53.0% utilized diagnostic services. Age, marital status, activities of daily living, and regular medication showed significant association with health services utilization at 95% level of confidence (p >0.05). Conclusion Marital status, daily living habits, existence of chronic disease, and regular medication demonstrated significant association with the utilization of health care. Social support services, informal education, and awareness programs targeting the senior citizens and studies covering a diverse population are recommended. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 34-39 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6911